A Community Devoted to the Preservation and Practice of Celestial Navigation and Other Methods of Traditional Wayfinding
From: Lars Bergman
Date: 2020 May 5, 11:59 -0700
As DaveP said, there are two possible solutions to
cos(azimuth - x) = cot(latitude)·tan(altitude)·cos(x), where tan(x) = csc(latitude)·cot(hour angle)
As cos(azimuth - x) = cos(x - azimuth) you get azimuth = x ± arccos[cot(latitude)·tan(altitude)·cos(x)], and x is the angle at zenith between the observer's meridian and a perpendicular to the body's meridian.